Impact of Exposure Period to Liquid Nitrogen Vapor on Criteria of Human Spermatozoa Cryopreserved in New Cryopreservation Technique - Ahmed H. Zwamel1 , Muhammad-Baqir M-R. Fakhrildin2 , Hayfa H. Hassani3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The emptied sheep’s ovarian follicles recently used as a container for spermatozoa during cryopreservation, it was found a proper carrier to cryopreserving spermatozoa in vapor-dependent cryopreservation. The aim of this study was to evaluate the effect of two periods of exposure to liquid nitrogen (LN2)vapor on the parameter of spermatozoa during cryopreservation in this technique. Method: The study was conducted on 30 semen samples from patients with oligozoospermia diagnosed by semen analysis according to the standard criteria of World Health Orgnization (WHO) 2010. Sheep’s ovarian follicles obtained from local slaughterhouse and prepared by slicing the ovaries and evacuating the follicular fluid and oocyte. Each semen sample diluted 1:1 with cryosolution (glycerol 10%) and injected within eight emptied sheep’s ovarian follicles. The first four follicles represent P1; exposed to LN2 vapor for 7.5 minutes and the other four follicles represent P2; exposed to LN2 vapor for 15 minutes before emerged in liquid nitrogen. Sperm progressive motility, total motility, normal morphology and DNA fragmentation index (DFI) were analyzed for all samples pre-freezing and post-thawing. Results: After two months of cryopreservation, sperm progressive motility and total motility significantly (P<0.01) increased post-thawing in P2 as compared with P1, while both of P1 and P2 significantly (P<0.01) decreased as compared with pre-freezing. Normal morphology significantly (P<0.01) decreased post thawing in both P1 and P2 as compared with pre-freezing, while no significantly difference foundbetween P1and P2. DFI significantly (P<0.01) increased post-thawing in P1 and P2 as compared with pre-freezing, while in P2 DFI was significantly lower than in P1. Conclusions: The exposure to liquid nitrogen vapor for 15 minutes in emptied ovarian follicles technique gives a better results than exposure to the vapor for 7.5 minutes regarding sperm progressive motility, total motility and DFI.